A Multi-Stimuli Responsive Spiropyran–Tetraphenylethene Conjugate for the Control of Near-Infrared Emission - Kar, Sajal; Chatterjee, Sheelbhadra; Bandyopadhyay, Subhajit (Synthesis, 2024)
The synthesis of a dinitrotetraphenylethene linked to two photochromic spiropyran moieties was achieved. The compound displays photochromic and acidochromic behavior. In the aggregated merocyanine photoisomeric state, the molecule is prone to form aggregates of the zwitterionic form. The merocyanine form displays near-infrared intense fluorescence (λmax_em. at 665 nm) extending into the near-infrared region up to 900 nm. On the other hand, the spiropyran form displays fluorescence in the 450 nm region. In DMF/water mixture, the near-infrared emission is quenched whereas the spiropyran form displays fluorescence with a λmax_em. at 563 nm.
Keywords: photochromism; spiropyran; acidochromism; aggregation; fluorescence